2011
DOI: 10.1136/ip.2010.030486
|View full text |Cite
|
Sign up to set email alerts
|

National five-year examination of inequalities and trends in emergency hospital admission for violence across England

Abstract: Analyses identify four lifetime periods for violence: up to 10 years (prepubescent), 11-20 years (adolescence), 21-45 years (younger adults), and over 45 years (older adults). While violence is most common in adolescence, its concentration in poorer areas during prepubescence and in younger adulthood (parenting age) suggests that poorer children are exposed to much more aggressive communities. This is likely to contribute to the disproportionate escalation in violence they experience during adolescence. Effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…Consequently, an industry with a concentration of individuals having acute and long-term health risks is perhaps not unexpected. However, consideration of childhood experiences brings into question whether even almost limitless resources in adulthood can undo the impacts of adverse childhoods, 32 or whether such resource can feed predispositions to risk behaviours. Rock and pop star survival also seems to relate to whether they have pursued successful solo careers (table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, an industry with a concentration of individuals having acute and long-term health risks is perhaps not unexpected. However, consideration of childhood experiences brings into question whether even almost limitless resources in adulthood can undo the impacts of adverse childhoods, 32 or whether such resource can feed predispositions to risk behaviours. Rock and pop star survival also seems to relate to whether they have pursued successful solo careers (table 3).…”
Section: Discussionmentioning
confidence: 99%
“…We selected demographic covariates to control for the potential confounding effect of age, sex, SES and status as an Aboriginal person based on findings from previous research 9 10. Data on each of these measures are maintained and regularly updated in the health insurance registry.…”
Section: Methodsmentioning
confidence: 99%
“…For example, meta-analysis of estimates from 34 studies showed that both homicide and assault, but not rape or robbery, were closely linked to poverty and income inequality 15. In England, an ecological study found that risk of violent injury was six times greater in deprived communities compared with affluent 16. Income inequality, measured using the Gini coefficient, has also been shown to have a positive effect on homicide and self-reported assault in a study of 169 low-income, middle-income and high-income countries, including the UK 17.…”
Section: Introductionmentioning
confidence: 99%